Effects of Multi-Muscle Electrical Stimulation and Stand Training on Stepping for an Individual With SCI - Momeni, Kamyar; Ramanujam, Arvind; Ravi, Manikandan; Garbarini, Erica; Forrest, Gail F. (Frontiers in Human Neuroscience, 2020)
The objective of this study was to evaluate the biomechanical, neural, and functional outcomes during a 10-minute treadmill stepping trial before and after two independent interventions with neuromuscular electrical stimulation (ES) in an individual with spinal cord injury (SCI). In this longitudinal study, a 34-year-old male with sensory- and motor-complete SCI (C5/C6) underwent two consecutive interventions: 61 hours of supine lower limb ES (ES-alone) followed by 51 hours of ES combined with stand training (ST) using an overhead body-weight support (BWS) system (ST+ES). Post ES-alone (unloaded), compared to baseline, the majority (~60%) of lower extremity muscles decreased their peak sEMG amplitude, while post ST+ES (loaded), compared to post ES-alone, there was a restoration in muscle activation that endured the continuous 10-minute stepping. Temporal α-motorneuron activity patterns were observed for the SCI participant. Post ST+ES, there were increases in spinal activity patterns during mid-stance at spinal levels L5-S2 for the right and left limbs. Moreover, post ES-alone, trunk stability increased with excursions from midline of base-of-support (50%) to left (44.2%; Baseline: 54.2%) and right (66.4%; Baseline: 77.5%). The least amount of trunk excursion observed post ST+ES, from midline to left (43%; AB: 22%) and right (64%; AB: 64%). Overall, post ES-alone, there were gains in trunk independence with a decrease in lower limb muscle activation, whereas post ST+ES, there were gains in trunk independence and increased muscle activation in both bilateral trunk muscles as well as lower limb muscles during the treadmill stepping paradigm. The results of the study illustrate the importance of loading during the stimulation for neural and mechanical gains.